A rapid, noninvasive immunoassay for frataxin: Utility in assessment of Friedreich ataxia - Deutsch, Eric C.; Santani, Avni B.; Perlman, Susan L.; Farmer, Jennifer M.; Stolle, Catherine A.; Marusich, Michael F.; Lynch, David R. (Molecular genetics and metabolism, 2010)
Friedreich ataxia (FRDA) is an autosomal recessive neurodegenerative disorder caused by reduced amounts of the mitochondrial protein frataxin. Frataxin levels in research studies are typically measured via Western blot analysis from patient fibroblasts, lymphocytes, or muscle biopsies; none of these is ideal for rapid detection in large scale clinical studies. Recently, a rapid, noninvasive lateral flow immunoassay was developed to accurately measure picogram levels of frataxin protein and shown to distinguish lymphoblastoid cells from FRDA carriers, patients and controls. We expanded the immunoassay to measure frataxin directly in buccal cells and whole blood from a large cohort of controls, known carriers and patients typical of a clinical trial population. The assay in buccal cells shared a similar degree of variability with previous studies conducted in lymphoblastoid cells (~10% coefficient of variation in controls). Significant differences in frataxin protein quantity were seen between the mean group values of controls, carriers, and patient buccal cells (100, 50.2, and 20.9% of control, respectively) and in protein extracted from whole blood (100, 75.3, and 32.2%, respectively), although there was some overlap between the groups. In addition, frataxin levels were inversely related to GAA repeat length and correlated directly with age of onset. Subjects with one expanded GAA repeat and an identified frataxin point mutation also carried frataxin levels in the disease range. Some patients displaying an FRDA phenotype but carrying only a single identifiable mutation had frataxin levels in the FRDA patient range. One patient from this group has a novel deletion that included exons 2 and 3 of the FXN gene based on multiplex ligation-dependent probe amplification (MLPA) analysis of the FXN gene. The lateral flow immunoassay may be a useful means to noninvasively assess frataxin levels repetitively with minimal discomfort in FRDA patients in specific situations such as clinical trials, and as a complementary diagnostic tool to aid in identification and characterization of atypical patients.